Needs, expectations, potentialities and weaknesses of leisure spaces in quilombola communities in Garanhuns-PE (Research, Society and Development, 2021)
The study aimed to identify the needs, expectations, strengths and weaknesses regarding leisure spaces in the Quilombola community Estivas-Garanhuns/PE. The research was characterized as exploratory and descriptive with a qualitative approach. Thirty residents participated in the survey. The interviews were recorded and later transcribed and the data were analyzed using content analysis. After analysis, two categories emerged, namely: needs and expectations; strengths and weaknesses of the quilombola community in terms of leisure space. The needs and expectations regarding leisure spaces emerged as a device that provides health. The indicated potentialities were the articulation of the leaders for the construction of the space with government bodies and religious leaders, as well as the existence of social equipment in the territory and recyclable materials in the community. The weaknesses were the lack of financial incentive from public agencies and the lack of greater mobilization of the community to build the leisure space. Through the conversation circle with the participants, elements were collectively proposed that would contribute to the construction of the action plan and development of the leisure space that will contribute to promoting the health of residents in a sustainable way.